Ankylosing Spondylitis and Postural Balance - Mehmet Adam; Berrin Leblebici; Alper Nabi Erkan; Selda Bağış; Mahmut Nafiz Akman (Archives of Rheumatology, 2008)
Objective: In this study, we aimed to investigate that, due to postural changes, the patients with ankylosing spondyilitis (AS) have poorer postural balance than healthy subjects. Materials and Methods: Thirty patients with AS (19 female, 11 male) and 20 healthy subjects (13 female, 7 male) were tested by using the Tetrax Interactive Balance System. The general stability, Fourier analysis showing patterns of sway intensity within eight frequency bands between 0.1 and 3 Hz, and weight distribution index (WDI) were evaluated. Data were also compared with disease duration and finger-floor distance, occiput-wall distance and Schober test. Statistical analyses were performed using SPSS 11.0 for Windows program. Mann-Whitney U test was used to compare groups and Pearson Correlation analysis was used for correlation. Results: There was no statistically significant difference on general stability, Fourier analysis scores, WDI between patients with AS and healthy subjects. A negative correlation was found between Schober test and general stability score. (r=-0,390 p=0,03). No other correlations were found between stability scores, Fourier analyses scores, WDI and occiput-wall distance, finger-floor distance and disease duration. Conclusion: The patients with AS have good postural balance. Disease duration and quantitative measurements of posture do not affect postural balance. (Rheumatism 2008; 23: 87-90)